Is Technical Analysis Profitable and Capable for Stock Price Prediction in Bursa Malaysia? - Lee, Kelvin Yong Ming (Universiti Malaysia Sarawak(UNIMAS), 2016)
This study aims to test the ability of technical analysis for predicting the stock price and generating profits. This study employed two of the technical analysis indicators, namely Variable Moving Average (VMA) rules and Elliott Wave Principle incorporated with Fibonacci sequences. Generally, over the full sample period, this study found that VMA rules were useful technical indicator in analysing the medium capitalization stocks and generating higher return. Besides that, VMA rules are further tested through the sub-sample test, out-of-sample test and regression analysis. Throughout the sub-sample test and out-of-sample test, this study also strengthens the evidence that VMA rules is successfully generating returns based on the medium capitalization stocks. Generally, this study found that 5 days was the most appropriate short term moving average for the analysis of the medium capitalization stocks. In addition, this study found that the signals emitted by all the VMA rules have significant relationship with the stock returns. As for Elliott Wave Principle incorporated with Fibonacci sequences indicator, this study found that the stock price movements of large capitalization can be predicted accurately as the prediction error during the impulsive wave is significantly less than 10 percent. However, the Elliott Wave Principle incorporated with Fibonacci sequences indicator is only successful in predicting the stock price movement during the pre- and post-crisis periods through the sub-sample test.